Evaluation of Cement Brick with Cocopeat as Partial Replacement of Sand - Lim, Yong Tat; Ling, Jen Hua; Bujang, Ummi Humaira Binti; Leong, Wen Kam; Sia, How Teck; Chiong, Mary Mee Shi (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2025)
The rising population has fueled construction growth, increasing the demand for bricks and raising concerns about the depletion of raw materials, especially sand. To address this, research was carried out to investigate the utilization of cocopeat (CCP) as a partial sand replacement in the construction industry. In this study, a total of 72 specimens were manufactured with varying proportions of cocopeat to replace sand, ranging from 0% to 25%. A 1:2.5 of cement-to-sand ratio and 0.5 of water-to-cement ratio were used. Performance of the cement brick was evaluated based on dimension, compressive strength, density, water absorption, crack development, and effective strength-to-weight ratio (  ratio). Results showed that all bricks met industrial requirements. Satisfactory compressive strength was achieved with 5% to 15% of cocopeat, meeting the minimum requirements in British Standard BS 3921:1985. Bricks with 5% to 10% of cocopeat have no crack on the sample. These bricks resulted in a lower density than solid bricks, while still fulfilled the percentage of water absorption requirements of British Standard, 1985. Cement bricks with 5% and 10% cocopeat had an effective strength-to-weight ratio (  ratio) above 1.0. Notably, brick with 10% cocopeat fulfilled all the industry requirements. Therefore, the cocopeat can be recommended as a partial replacement in brick production.